Peran E-satisfaction dalam Memediasi Pengaruh E-service Quality Terhadap E-loyalty Pelanggan pada Toko Online Cilufio - Ninin Non Ayu Salmah; Suhada Suhada; Reina Damayanti (Universitas Batanghari Jambi, 2021)
This study aims to test the hypothesis of the effect of e-service quality on e-loyalty through the mediating variable e-satisfaction. The population of this research is all customers who have bought cosmetic products at Cilufio Online Shop. The sampling technique is purposive sampling with the criteria of customers who have made purchases at least 2 times and have recommended Cilufio Online Shop to others, the total sample is 74 respondents. The research data analysis technique uses inferential statistical methods, path analysis and Sobel Test. E-service quality and e-satisfaction are exogenous variables and e-loyalty as endogenous variables. The results of the hypothesis test conclude that simultaneously there is a variable effect of e-service quality and e-satisfaction on e-loyalty, partially there is an effect of the e-service quality variable on e-loyalty and there is an influence of the e-satisfaction variable on customer e-loyalty Cilufio online Shop. The effect of total e-service quality through e-satisfaction on e-loyalty is greater than the direct effect of e-service quality on e-loyalty, which means that e-satisfaction is a mediating variable of e-service quality on e-loyalty of customers at Cilufio online shop. The results of the Sobel Test show a significant mediation coefficient, which means that e-service quality has an effect on e-loyalty through e-customer satisfaction at Cilufio Online Shop.